Treatment of an Atypical Case of Bilateral Nephrolithiasis in a Canine - Rovaris, Inácio Bernhardt; Gouvêa, Aline Silva; Tisotti, Tainor de Mesquita; Schaefer, Gabriela da Cruz; Monteiro, Eduardo Raposo; Alievi, Marcelo Meller (Acta Scientiae Veterinariae, 2020)
Background: Less than 5% of canine uroliths are found in the kidney and ureter. The decision to remove a nephrolith is controversial and should be considered in cases of refractory infection, hematuria, presence of obstructive uropathy and compression of the renal parenchyma. The aim of this report is to describe an unusual presentation of bilateral nephrolithiasis in a dog, occupying almost the entire renal parenchyma, its clinical and imaging findings, in addition to surgical treatment and its evolution. Case: A 10-year-old male Basset Hound was evaluated at the Veterinary Medical Teaching Hospital (HCV) of the Federal University of Rio Grande do Sul (UFRGS), presenting prostration, anorexia, vomiting, diarrhea and severe hematuria for three days. On physical examination the patient was dehydrated, with pale mucous membranes, uremic breath and abdominal pain. Blood tests showed mild anemia and azotemia. In both kidneys, abdominal ultrasonography exhibited a large hyperechoic structure with deep acoustic shadowing. These same structures were observed in abdominal radiographic examination as radiopaque structures, confirming the diagnosis of bilateral nephrolithiasis. Urine culture was positive for coagulase-negative Staphylococcus sp. The patient was stabilized with fluid therapy, antiemetic, analgesics, antibiotics and whole blood transfusion. Unilateral nephrotomy of the right kidney was performed to remove the urolith. After three months, nephrotomy of the left kidney was performed to remove the other urolith. The patient was clinically stable and with no macroscopic hematuria 12 h after surgery. Two days after discharge, the patient returned prostrated in lateral recumbency, however with no alteration of parameters in physical examination. Blood tests showed anemia, thrombocytopenia, hypoalbuminemia, azotemia and hyperphosphatemia. The dog presented a convulsive episode and died shortly, eight hours later. In the necropsy examination, extensive loss of renal parenchyma was seen in both kidneys and the presence of thrombosis and areas of infarction in several organs such as spleen, liver, lungs and central nervous system. Discussion: Complications of nephrotomy include perirenal hemorrhage, hydronephrosis due to obstruction of blood clots or urine leakage to the abdominal cavity. From the necropsy findings, the surgical site did not present these complications, justifying that the surgical procedure was not directly related to death. Correction of dehydration, blood transfusion, and antibiotic therapy based on urine culture and susceptibility testing was important for initial stabilization, before surgery. However, the presence of advanced chronic kidney disease may have contributed to deterioration of the patient's clinical condition and death. The presence of thrombus and hemorrhagic areas, observed during necropsy, associated with acute onset of clinical signs and the presence of severe hypoalbuminemia, may suggest that the patient died due to a thromboembolic event, as a consequence of nephrotic syndrome. Studies show that nephrotomy can be performed with few adverse effects on renal function if the surgical technique and anesthetic management are adequate. In this case, nephrotomy was the best option for the treatment of the patient, since it enabled a rapid intervention, controlled the hematuria and allowed the removal of both uroliths without complications related to surgery.